Musical Rhythm in Poetry ‘Al-Jaddu Yudni Kulla Amr Syasi’in’ by Imam Syafi’i (Critical Analysis of ‘Arudh and Qowafi)|Irama Musikalitas pada Puisi ‘Al-Jaddu Yudni Kulla Amr Syasi’in’ Karya Imam Syafi’i (Analisis Kritik Sastra Arudh dan Qowafi) - Abdul Latif; Faidatul Jannah (Mantiqu Tayr: Journal of Arabic Language, 2022)
Imam Syafi'i is well known as a jurist, but he also has works in the field of literature. His literary works in the form of poetry are composed using the rules of arudh and qawafi. In the rules of Arabic poetry, the rhythm of the musicality of a poem is determined by the consistency of using the rules of Arudh and Qawafi, therefore the purpose of this study is to find the rhythm of musicality and analyze the shortcomings and advantages of the poetry of the Shafi'i imam with a descriptive qualitative method. The results of this study found two rhythms of musicality that exist in this poem, namely using the types of bahr Kamil and Rojaz. His qafiyah takes the form of a part of the word from the final fragment of the verse of the poem. This poem also has several advantages, namely, the first stanza to the end has the same wazan taf'ilah and the qawafi reads the letter ق and is in the form of a part of the word, and in the second stanza, when viewed from the type of bahr Rojaz then the wazan taf'ilah is free from zihaf. While the drawback is that in the first stanza to the end there is a zihaf al-idhmar that enters it, in the qawafinya where the fourth and fifth stanzas of the qafiyah there is zihaf al-idhmar, and in the third stanza the final sound of the stanza is different from the other stanzas, with fathah tone. This research shows that although better known as a jurist, Imam Shafi'I also has literary works that have a high musical rhythm value.